The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/cancers14071602
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Therapy in Integrated Oncology and Palliative Cancer Care: An Observational Study

Abstract: Decision-making for antibiotic therapy in palliative cancer care implies avoiding futile interventions and to identify patients who benefit from treatment. We evaluated patient-reported outcome-measures (PROMs), physiological findings, and survival in palliative cancer care patients hospitalized with an infection. All acute admissions during one year, directly to a University Hospital unit that provided integrated services, were included. Serious infection was defined as a need to start intravenous antibiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…PN may result in a variety of treatment-related complications, like hyperglycemia, refeeding syndrome, thrombosis, and serious infections [32]. We previously demonstrated that approximately one-quarter of the patients acutely admitted to the APCU received intravenous antibiotics [33]. Taking the inherent limitations of a short observation period and a restricted number of patients into account, we were not able to detect any difference in infection prevalence for hospitalized patients treated with PN compared to patients not receiving this intervention.…”
Section: Pn and Complicationsmentioning
confidence: 81%
“…PN may result in a variety of treatment-related complications, like hyperglycemia, refeeding syndrome, thrombosis, and serious infections [32]. We previously demonstrated that approximately one-quarter of the patients acutely admitted to the APCU received intravenous antibiotics [33]. Taking the inherent limitations of a short observation period and a restricted number of patients into account, we were not able to detect any difference in infection prevalence for hospitalized patients treated with PN compared to patients not receiving this intervention.…”
Section: Pn and Complicationsmentioning
confidence: 81%